INCREASING VOCABULARY MASTERY OF THE TENTH GRADE STUDENTS AT SMK NEGERI 1 GALANG THROUGH SONG - Darwin Darwin (Universitas Madako Tolitoli, 2018)
This research belongs to experimental design with pre-test and post-test activity. The objective of the research is to find out how Song can increase the students’ achievment in vocabulary mastery. Sample of the research were 25 students’ of tenth grade of SMK Negeri 1 Galang. In doing this research, the researcher used a media or Song of production. The data analysis of the research was quantitative measurement to find the mean. Based on the data analysis from pre-test and post-test activity. Based on the result, it was found that the use of Song in teaching English is effective to increase the students’ vocabulary mastery and very beneficial for the students in order to facilitate them in learning English. Based on this finding, it is suggested that Song in teaching English can be recommended for the English taecher. but the English teacher should select appropriate Song to the students’. Keywords : increasing, Vocabulary, Mastery, Song.